2016
DOI: 10.1126/sciadv.1600567
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial microfluidic droplet engineering for biomimetic material synthesis

Abstract: Combinatorial chemical evolution is used to select oil-water droplet interfaces that drive inorganic nanoparticle synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 63 publications
0
54
0
Order By: Relevance
“…They are multifunctional units that can perform locomotion, sensing, capture, and release . Further, combinatorial microfluidics is used to create a droplet generation platform with enhanced stability to synthesize biomimetic materials for various applications …”
Section: Introductionmentioning
confidence: 99%
“…They are multifunctional units that can perform locomotion, sensing, capture, and release . Further, combinatorial microfluidics is used to create a droplet generation platform with enhanced stability to synthesize biomimetic materials for various applications …”
Section: Introductionmentioning
confidence: 99%
“…These reactions are catalyzed extremely efficiently to produce various special substances; therefore, the investigation of cells is highly significant for multidiscipline. In recent years, the fabrication of artificial biomimetic materials has attracted a great deal of attention . Attributed for the development of materials science and engineering science, various artificial organs, such as heart, blood vessels, liver acinus, skin, muscle, and nerve, have been fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a number of reviews about microfluidic fabrication of materials have been reported from different aspects, which mainly refer to certain microfluidic technologies (e.g., droplet microfluidics) or specific forms of materials (e.g., microparticles) . However, a comprehensive review that puts the attention on microfluidic fabrication of NMs and their biomedical applications is unavailable.…”
Section: Introductionmentioning
confidence: 99%